Lilium pseudonanum (Liliaceae), a Rare and Cryptic Species From Southeast Xizang, China - Xiaojuan Chen; Yumei Yuan; Yundong Gao (Ecology and Evolution)
ABSTRACT Lilium pseudonanum, a new species endemic to highly restricted habitats in the eastern Himalayas, has been identified and taxonomically distinguished from the morphologically similar L. nanum. Genetic analyses utilizing nuclear and chloroplast datasets have conclusively established L. pseudonanum as a distinct species, revealing a complex relationship with L. nanum and other related taxa, despite the historical classification of the former two as conspecific. Genomic evidence suggests a potential hybrid origin for L. pseudonanum. Nuclear‐plastid discordance indicates chloroplast capture from the Duchartrei clade and nuclear introgression from the Lophophorum clade. Furthermore, ADMIXTURE analyses reveal a tripartite ancestry, while TreeMix analysis has detected bidirectional gene flow from both putative parental lineages. In contrast, morphological principal component analysis (PCA) has shown no significant differences between the two species, except for the notably larger basal leaf blades in L. pseudonanum, highlighting its cryptic nature. Ecologically, L. pseudonanum occupies habitats characterized by higher summer precipitation and prolonged snow accumulation during winter, providing greater moisture availability compared to the drier habitats of L. nanum. This suggests a degree of ecological niche divergence between the two species. Environmental niche modeling (ENM) predicts that the distribution of L. nanum may shift in response to global warming, potentially driving its upward migration to higher elevations or latitudes. This northward or altitudinal movement could lead to overlapping habitats with L. pseudonanum, raising critical concerns about habitat loss and the risk of genetic introgression. Such introgression could threaten the taxonomic distinctiveness and ecological stability of L. pseudonanum. Given its extremely restricted geographic range and small population size, L. pseudonanum has been classified as “Critically Endangered” (CR). As a result, urgent actions are needed to confirm its taxonomic status and implement comprehensive conservation measures to ensure its survival.